Anticoagulation-Associated Bleeding in Patients Screened for Atrial Fibrillation versus Usual Care—A Post Hoc Analysis from the LOOP Study - Kongebro, Emilie Katrine; Diederichsen, Søren Zöga; Xing, Lucas Yixi; Haugan, Ketil Jørgen; Graff, Claus; Højberg, Søren; Olesen, Morten S.; Krieger, Derk; Brandes, Axel; Køber, Lars; Svendsen, Jesper Hastrup (TH Open, 2024)
Background Atrial fibrillation (AF) prevalence is rising; however, data on the bleeding risks associated with the detection of subclinical AF are needed.Objective Our objective was to determine the bleeding increment associated with implantable loop recorder (ILR) screening for subclinical AF and subsequent anticoagulation initiation compared with usual care.Methods This post hoc study utilized LOOP trial data from 6,004 elderly patients with stroke risks randomized to either ILR (n = 1,503) or usual care (n = 4,503). The mean follow-up time was 64.5 months, and none were lost to follow-up. The primary exposure was the initiation of oral anticoagulation, and the main outcome was the risk of major bleeding events following initiation of oral anticoagulants (OACs), determined by time-dependent cox regression. Second, we investigated antithrombotic prescription patterns and major bleeding events after antiplatelet treatment and in subgroups.Results OAC was initiated in 1,019 participants with a mean age (years) of 78.8 (± 4.67) in control versus 77.0 (± 4.84) in ILR, p < 0.0001. Altogether did 202 participants end or pause OAC treatment. Among AF patients (n = 910) had 40 (28%) completely ended OAC and 105 (72%) temporarily paused OAC during follow-up. Major bleeding events totaled 221 (3.7%). Forty-seven major bleeding events followed an OAC initiation in 1,019 participants (4.6%); 26 versus 21 events in the control and ILR groups, respectively. The hazard ratio (HR) for major bleeding after OAC initiation compared with before initiation was 2.08 (1.50–2.90) p < 0.0001 overall, 2.81 (1.82–4.34) p < 0.0001 for control and 1.32 (0.78–2.23) p = 0.31 for the ILR group (p = 0.07 for interaction). Antiplatelet treatment resulted in an overall adjusted HR of 1.3 (0.96–1.75) p = 0.09. For OAC users aged ≥75 years in the ILR group, the rate of major bleeding was 1.73 (0.92–2.96) compared with 0.84 (0.36–1.66) for an age <75 years, and the rate of the corresponding control subgroup aged ≥75 years was 2.20 (1.23–3.63) compared with 1.64 (0.82–2.93) for an age <75 years.Conclusion The individual risk of major bleeding increased twofold after initiation of oral anticoagulation for all patients in this study. However, the patients screened for subclinical AF did not have a higher bleeding risk after initiation of anticoagulation compared with those in usual care.Trial Registration: The LOOP study is registered at ClinicalTrials.gov, identifier: NCT020364 50
Keywords: major bleeding; subclinical atrial fibrillation; implantable loop recorder screening; oral anticoagulation